The AGTR2 rs11091046 (A>C) polymorphism and power athletic status in top-level Brazilian athletes - Guilherme, J. P. L. F.; Sussi Silva, M.; Bertuzzi, R.; Lancha Junior, A. H. (Journal of Sports Sciences, 2019)
The main purpose of this study was to investigate if the rs11091046 (A>C) polymorphism in AGTR2 gene is associated with athletic status in top-level athletes from Brazil. Since the AGTR2 gene is located on the X chromosome, the case-control association study was done separately for women and men. The female cohort was composed of 205 athletes and 241 non-athletes, and the male cohort was composed of 419 athletes and 490 non-athletes. We did not identify an association between the C-allele and the endurance phenotype. However, power athletes had a higher frequency of the A-allele. In women, A/A genotype was overrepresented in international-level power group compared with non-athletes or international-level endurance athletes (23.2% vs. 16.6% or 8.8%, respectively; p < 0.05). In men, the A-allele frequency observed in power athletes or international-level power athletes was statistically different from that observed in non-athletes (51.6% or 57.8% vs. 40.4%; p < 0.009). Furthermore, men sprinters with the A-allele showed significantly faster personal best times for the 100 m than those with the C-allele (10.56 ± 0.32 s vs. 10.93 ± 0.49 s; p < 0.02). In conclusion, it was found that the AGTR2 A-allele is a candidate genetic marker for top-level power athletes.